1967
DOI: 10.1136/bmj.1.5540.631-e
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia: complications of its surgical treatment.

Abstract: to be able to provide the complementary portion. Since this situation can lead, as it has in the past, only to mutual recriminations, I can only deprecate the impression you have given. The same of course applies to any combined procedure in which two or more specialties are involved.-I am, etc.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1976
1976
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Epistaxis and anaesthetic ulcers follow this selfinfiicted trauma (Cliffe & Demis, 1967;Sorger, Mayr & Pehamberger, 1981). The true incidence of neurotrophic ulceration following section ofthe Gasserian ganglion is difficult to estimate as trophic lesions involving the analgesic skin may more often be seen by dermatologists than by neurologists and neurosurgeons (Freeman, 1967). In a comprehensive study ofthe results of surgical treatment in 650 patients with trigeminal neuralgia, ulceration of the skin of the face and nostril was reported in 12 out of 66 (i8"n) patients with permanent anaesthesia following tbe injection of alcohol into the Gasserian ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…Epistaxis and anaesthetic ulcers follow this selfinfiicted trauma (Cliffe & Demis, 1967;Sorger, Mayr & Pehamberger, 1981). The true incidence of neurotrophic ulceration following section ofthe Gasserian ganglion is difficult to estimate as trophic lesions involving the analgesic skin may more often be seen by dermatologists than by neurologists and neurosurgeons (Freeman, 1967). In a comprehensive study ofthe results of surgical treatment in 650 patients with trigeminal neuralgia, ulceration of the skin of the face and nostril was reported in 12 out of 66 (i8"n) patients with permanent anaesthesia following tbe injection of alcohol into the Gasserian ganglion.…”
Section: Discussionmentioning
confidence: 99%
“…foram identificadas em apenas seis doentes, valor inferior ao observado após outros procedimentos ablativos para tratar a NIT (Freeman, 1967;Dicken, 1997;Kavanagh et al, 1996;Urabe et al, 1999;Ferrara et al, 2000;Sadeghi et al, 2004). As lesões mucosas e cutâneas são decorrentes do comprometimento da sensibilidade superficial e dos traumatismos repetidos e facilitam a instalação de doenças infecciosas orais incluindo a candidíase e podem simular infecções (sífilis, lesão herpética, hanseníase, blastomicose, paracoccidioidomicose, leishmaniose, tumores) (Cliff e Demis, 1967;Goodnight e Calcaterra, 1994).…”
Section: Totalunclassified
“…I had postulated that ulceration of the face with erosion of the ala nasi after the injection of alcohol into the Gasserian ganglion, sensory root section of the trigeminal nerve, and in other patients with interruption of the peripheral or central sensory pathways of the trigeminal nerves were self-induced (Freeman, 1966). 821 I have also seen quite a few patients who have developed ulceration of the skin of the forehead and scalp after herpes zoster and suggested that these so-called trophic lesions involving the analgesic skin may be more often seen by our dermatological colleagues than by neurologists and neurosurgeons, and that their true incidence is far greater than the paucity ofreports in the neurological literature would suggest (Freeman, 1967). I have also reported clinical details of two patients with acute vascular disorders of the brain stem who later developed progressive ulceration of the skin of the face with cartilaginous destruction of the nostril.…”
Section: J a Simpsonmentioning
confidence: 99%